Designing a Sustainable Strategy for the Exploitation of Social Media by Networkers - Susi, Antonio Alessandro (My University, 2017)
Internet revolution brought some considerable changes in the business environment, ensuring a new way of approaching to activities online. Social media development in last decades has revealed a specific area of interest for the ventures involved in the web environment. The specific design of those tools has enabled faster and easier connections among users, creating an information filled setting reliant on constant interactions and communications. A very peculiar activity that has been influenced by those circumstances is network marketing. This specific business has characteristics that fit well the net establish by the internet. Furthermore, the digital context represents a huge opportunity since it includes some tools and resources that make more effective and efficient the process through data analysis and usage combined with easiness in communications. This study investigates the characteristics of network marketing activity and online context to develop a strategy for the sustainable usage of social media in that job. The pillars of MLM are represented by the knowledge sharing and the need of establishing strong and reliable relationships with consumers. Online environment is for its nature a perfect place for information sharing and management, moreover enabling communications it is possible to create commitment with customers. The two main objectives of a networkers, selling and recruiting, are achievable through the usage of social media. Exploiting the latter establishes a peculiar way of undertaking the activity, making it easier and effective, especially if a consistent strategy is followed. Results show that a sustainable strategy firstly relies on information and relationships management. Moreover, every social medium has to be very specialized on few tasks directly related with the networker’s objectives. All the social media’s functions require to be linked each other in order to obtain a coherent and well developed process that could cover the needs for the accomplishment of the objectives. Interviews with a pool of networkers already involved in the online exploitation, validating theoretical concepts, have helped the researcher to design a blueprint which could help in carry out the job.
Keywords: Network Marketing; Social Media; Strategy; Sustainable Competitive Advantage; Networker; fi=Master's Degree Programme in International Business|